Peran Algoritma Media Sosial dalam Pembentukan Tren Musik: Studi Tentang Lagu Viral di TikTok - Hakim, Putri Nabila (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2024)
This study examines the role of TikTok's algorithm in shaping global music trends and song virality through a qualitative approach. TikTok uses a machine learning-based recommendation system that analyzes user interactions, such as watch time and social participation, to promote content. The research finds that TikTok’s algorithm not only curates but also predicts the potential virality of songs, particularly popular music genres like pop and hip-hop. Additionally, geographic bias was identified, with artists from the United States and Europe having a higher likelihood of going viral compared to artists from other regions. While TikTok provides opportunities for independent musicians, the sustainability of viral song popularity remains a challenge. These findings highlight significant shifts in music promotion strategies, with the algorithm becoming a key element in the modern music ecosystem. The study suggests the need for continuous adaptation by artists and industry players in the digital era.